(untitled) (Bangladesh Journal of Medical Science, 2018)
Aims: To correct the Angle class I malocclusion with crowding via four premolar extractions. Presentation of case:A 19-year-old Malaysian female presented with the bimaxillary protrusion, crowding, high canines, midline deviation and edge-to-edge anterior bite. Upper lateral incisors were palatalized and in crossbite interactions with the opposite teeth. Discussion: Treatment was initiated using fixed orthodontic appliances followed by four 1st premolar extractions in both arches. Case was finished with good inter cuspation of the upper and lower teeth. Molars were finished in a Class I relationship with canine guidance, and ideal overjet and overbite were obtained. Conclusion: Successful finishing of a case with beautiful smile, obtained proper overjet and overbite, corrected cross bite, midline shifting and the improved soft tissue profile. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.683-687